Intellectual Property Rights Guarantee: Roles and Challenges for Notaries - Niken Eka Marthasari (Journal of Law, Politic and Humanities, 2025)
Exclusive rights in intellectual property as intangible movable objects can be used as objects of fiduciary collateral based on statutory regulations, although positive law has regulated that IPR can be used as collateral, in practice it is still not widely implemented, because of the incomplete legal certainty regarding the assessment mechanism,  limited time period for IPR apprentices, as well as further regulations regarding the execution of guarantees in the event of breach of contract or default.  The role of a notary is very important as a general official who makes fiduciary guarantee deeds, of course it is a challenge for notaries to be able to understand the implementation of fiduciary guarantees in the form of IPR.  This writing aims to find out more about the systematics of fiduciary guarantee deeds with IPR objects, as well as the role and challenges of notaries as makers of fiduciary guarantee deeds with IPR objects.  The method used is doctrinal or normative research, with an approach to positive legal regulations. This research is explanatory, which aims to test theories and hypotheses related to the application of IPR as fiduciary collateral